2020
DOI: 10.1002/qute.201900120
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Antennas

Abstract: Due to the recent groundbreaking developments of nanotechnologies, it became possible to create intrinsically quantum systems able to serve as high-directional antennas in terahertz, infrared, and optical ranges. In fact, the quantum antennas, as devices shaping light on the level of single quanta, have already become key elements in nanooptics and nanoelectronics. The quantum antennas are actively researched for possible implementations in quantum communications, quantum imaging and sensing, and energy harves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 270 publications
(417 reference statements)
0
18
0
Order By: Relevance
“…Therefore, L plays the role of the infinitesimal generator of stochastic evolution in the open dynamics of quantum systems. 5 Under some general but standard assumptions, 6 it can be shown that the following master equation is the most general one that can lead to trace-preserving and completely positive evolution of the density operator 7 [15], [24]:…”
Section: Time-domain Evolution Through the Master Equation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, L plays the role of the infinitesimal generator of stochastic evolution in the open dynamics of quantum systems. 5 Under some general but standard assumptions, 6 it can be shown that the following master equation is the most general one that can lead to trace-preserving and completely positive evolution of the density operator 7 [15], [24]:…”
Section: Time-domain Evolution Through the Master Equation Methodsmentioning
confidence: 99%
“…Quantum antenna theory is an emerging new field within the larger area of quantum technologies [1], [2] and optical antennas [3], [4], itself part of quantum engineering [5]. The main objective of quantum antenna theory is to understand the fundamental principles of quantum antennas relative to classical antennas [6], [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum systems consisting of a set of quantum emitters, i.e., quantum antennae, have recently attracted great interest [1]. A quantum formalism must be used to describe such systems because quantum antennae possess several specifi cs atypical of classical analogs.…”
Section: Introductionmentioning
confidence: 99%
“…= kΔ sin φ 1 and (1) 2 ϕ = kΔ sin φ 2 that describe points where the correlation function [Eq. ( 14)] of the quantum antenna consisting of three and four atoms is equal to zero.…”
Section: Introductionmentioning
confidence: 99%